2004
DOI: 10.1002/gcc.20057
|View full text |Cite
|
Sign up to set email alerts
|

ERBB2, TBX2, RPS6KB1, and MYC alterations in breast tissues of BRCA1 and BRCA2 mutation carriers

Abstract: Breast cancer risk is greatly increased in women who carry mutations in the BRCA1 or BRCA2 genes. Because breast cancer initiation is different between BRCA1/2 mutation carriers and women who do not carry mutations, it is possible that the mechanism of breast cancer progression is also different. Histopathologic and genetic studies have supported this hypothesis. To test this hypothesis further, we utilized a large cohort of women who underwent therapeutic mastectomy (TM) and contralateral prophylactic mastect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
35
4

Year Published

2004
2004
2017
2017

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 46 publications
(48 citation statements)
references
References 29 publications
9
35
4
Order By: Relevance
“…On the other hand, the ERBB2 subtype comprised only of BRCAX tumors (four cases, B14%) (Table 1). This finding is in concordance with the low incidence of ERBB2 amplification in BRCA1/2 mutation carriers described before (Grushko et al, 2002;Lakhani et al, 2002;Palacios et al, 2003;Adem et al, 2004). A significant association was found between most of BRCAX samples (45%) and luminal A phenotype, as seen in previous analyses (Oldenburg et al, 2006;Honrado et al, 2007).…”
Section: Discussionsupporting
confidence: 90%
“…On the other hand, the ERBB2 subtype comprised only of BRCAX tumors (four cases, B14%) (Table 1). This finding is in concordance with the low incidence of ERBB2 amplification in BRCA1/2 mutation carriers described before (Grushko et al, 2002;Lakhani et al, 2002;Palacios et al, 2003;Adem et al, 2004). A significant association was found between most of BRCAX samples (45%) and luminal A phenotype, as seen in previous analyses (Oldenburg et al, 2006;Honrado et al, 2007).…”
Section: Discussionsupporting
confidence: 90%
“…No cases showed amplification of both HER2 and MYC. These results are in contrast to those obtained by Adem et al, 62 who found a high prevalence of MYC duplications (57%) but a low frequency of amplification (8%) among invasive carcinomas from BRCA1/2-deleterious mutation carriers.…”
Section: Myc and Myb Amplificationcontrasting
confidence: 99%
“…Further, TBX2 is upregulated in a subset of breast cancer cell lines, and breast tumors with mutations in BRCA1 and BRCA2 (7,(20)(21)(22), which are strongly associated with ovarian serous carcinoma.…”
Section: Discussionmentioning
confidence: 99%